"In Other Business": A Review of Dr. Keri Day's Unfinished Business: Black Women, the Black Church, and the Struggle to Thrive in America. Issue 3 (19th November 2014) - Bridgeman, Valerie
Abstract : In this book, Dr. Keri Day addresses the challenges religious communities face in being a site of both support and shaming for poor people, especially book black women. In an effort to understand how race affects the way aid and empowerment occurs for black women made poor, Day analyzes faithbased programs and government-led programs designed to help mitigate poverty. In the end, she begins to offer a way forward that is neither demeaning nor debilitating for women who strive to thrive in communities.